Biosynthesis of reduced graphene oxide using Turbinaria ornata and its cytotoxic effect on MCF‐7 cells - K. M. Smita; L. Stanley Abraham; V. Ganesh Kumar; Raguraman Vasantharaja; R. Thirugnanasambandam; Ajit Antony; K. Govindaraju; T. Senthil Velan (IET Nanobiotechnology)
Abstract Graphene‐based nanomaterials are gaining importance in biomedicine because of their large surface areas, solubility, and biocompatibility. Green synthesis is the most economical method for application, as it is rapid and sustainable. Biofunctionalized reduced graphene oxide (TrGO) nanosheets were synthesized using methanol extract of Turbinaria ornata, and bioreduction of graphene oxide was primarily confirmed and characterized using UV‐visible, Fourier transform infrared (FTIR), and X‐ray diffraction spectroscopy and further characterized by zeta potential and transmission electron microscopy. The FTIR spectra of TrGO showed a decrease in the band intensities of oxygen groups, thus confirming effective deoxygenation. The zeta potential value of −34.6 mV revealed that synthesized TrGO was highly stable. The cytotoxic effect of TrGO against MCF‐10A and MCF‐7 cells was ascertained using MTT assay, showed a greater cytotoxic effect on MCF‐7 cells. The IC50 of TrGO treatment against MCF‐7 was calculated to be 31.25 µg, which is onefold lower than the cytotoxic effect of methanolic extract of T. ornata (60.0 ± 1.14 µg/ml). In addition, there was a statistically significant difference in cell viability between MCF‐10A and MCF‐7 cells in the treatment of TrGO. Hence, this study results in an efficient green reductant for producing rGO nanosheets that possess cytotoxicity against breast cancer cells.